Tumorigenic potential of mononucleated small cells of Hodgkin lymphoma cell lines - Ikeda, Jun-ichiro; Mamat, Suhana; Tian, Tian; Wang, Yi; Rahadiani, Nur; Aozasa, Katsuyuki; Morii, Eiichi (2010)
Tumor cells with tumorigenic potential are limited to a small cell population known as cancer stem cells (CSCs). CSCs yield both CSCs and non-CSCs, whereas non-CSCs do not yield CSCs. CSCs have not been identified in any malignant lymphomas. Hodgkin lymphoma (HL) is a mostly B-cell neoplasm that can be diagnosed by the presence of multinucleated (Reed-Sternberg; RS) cells admixed with Hodgkin cells with distinct nucleoli and various inflammatory cells. Here, the tumorigenic potential of cells with a single nucleus (S) and cells with multiple nuclei (M), which may be equivalent to Hodgkin and RS cells, respectively, was examined in HL cell lines L1236 and L428. Cultures of single S cells yielded both S and M cells, whereas M cell cultures yielded only M cells. When either cultured in methylcellulose or inoculated into NOD/SCID mice, the colony number and tumor size were both larger in S than in M cells. Concentrations of intracellular reactive oxygen species (ROS) were at low levels in a portion of S cells that abundantly expressed FoxO3a, a transcription factor that regulates ROS-degrading enzymes. In clinical samples of HL, FoxO3a was expressed in mononuclear Hodgkin cells but not in multinucleated RS cells. These findings suggest that smaller cells or Hodgkin cells that show low-ROS concentrations and high FoxO3a expression levels might be candidates for HL CSCs.